Pro-Poor and Gender Responsive Disaster Financing System in Nepal: A Case Study of Dhangadhi Sub-Metropolitan City - Shrestha, Nabin (Journal of Social Protection, 2023)
Nepal has made considerable progress in the formulation of disaster-resilient development policies and legal frameworks. However, how such policies have not translated into actions, and financing mechanisms, while governance too remains a prominent issue, which is less discussed in the disaster risk reduction and management sector. As the impact of disasters is disproportional to poor, vulnerable, and deprived groups of the society, disaster financing strategies must have considered pro-poor and gender-sensitive approaches to mitigate, minimize disaster risks, and develop resilient actions. But very limited studies have highlighted critical gaps in pro-poor and gender-responsive (PPGR) disaster financing mechanisms at the sub-national level. This paper draws on both qualitative and quantitative approaches to examine the disaster risk financing tools, policies, practices, and challenges of PPG Rin disaster budgeting at local levels. The study reflects that Dhangadi Sub Metropolitan City has practiced both ex-post and ex-ante-disaster financing tools to cope with the impact of disaster events. The PPG Ranalysis indicated that over three-quarters of the disaster risk reduction and management budget is indirectly gender-responsive whereas only 10per cent of the budget is directly responsive in both fiscal years (2018 &2019). Similarly, the entire disaster risk management budget is in directly pro-poor responsive. The absence of PPGR-specific guidelines, knowledge and skill gaps on the budgeting, and the lack of explicitly articulated disaster, gender, and poverty reduction targets and indicators are the main challenges hindering the implementation of a pro-poor and gender-responsive disaster financing system at the local level.